Existence of Periodic Solutions in Impulsive Differential Equations (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we are concerned with the problem of existence ofperiodic solutions for a class of second order impulsive differential equations.By Poincaré-Bohl theorem, we give several criteria to guarantee that the impulsive differential equation has periodic solutions under assumptions that thenonlinear term satisfies the linear growth conditions. Two specific examplesare presented to illustrate the obtained results.